Multidimensional comparative analysis of the number of students in Poland with the view to the demographic crisis and its impact on social security - Aleksandra Skrabacz; Bartosz Kozicki; Paweł Jaśkiewicz (Journal of Modern Science)
Objectives The article presents the original multidimensional comparative analysis of the number of students in terms of their population in Poland with the view to the demographic crisis and its impact on the acceptable level of social security. The demographic low in Poland is one of the largest in the European Union and the largest after the Second World War.